On-demand continuous H2 release by methanol dehydrogenation and reforming via photocatalysis in a membrane reactor. Issue 21 (10th October 2022) - Jiao, Haimiao; Yang, Jianlong; Li, Xiyi; Wang, Chao; Tang, Junwang
Abstract : A robust flow membrane reactor is established and utilised for efficient green H2 production in photocatalytic methanol dehydrogenation and reforming, benefiting from its enhanced mass transfer and effective charge separation in the catalysts. Abstract : Photocatalytic methanol dehydrogenation and reforming is viewed as a promising strategy to realize H2 production on demand. Herein, we report highly dispersed Cu x O nanoparticles on TiO2 (PC50) for continuous H2 production from aqueous methanol solution by photocatalysis in a flow reactor at a low temperature and under atmospheric pressure. The flow membrane reactor improves the H2 production rate by a factor of 1.63 compared with the widely used batch reactor thanks to enhanced mass transfer. Furthermore, the optimized 1% Cu/PC50 exhibits a 17-times higher H2 yield (33 702 μmol g −1 h −1 ) than pristine PC50. The apparent activation energy on 1% Cu/PC50 is found to be halved to as low as 4.0 kJ mol −1, which is much less than those in other methanol reforming processes. The diverse characterisation proposes that Cu x O as electron acceptors could effectively promote charge separation and work as active sites for the reduction reaction, together with the improved mass transfer in the reactor leading to enhanced photocatalytic performance.